Gestão por competências e desempenho coletivo: análise da Secretaria de Gestão de Pessoas no Tribunal de Justiça do Amazonas - Pinheiro, Vinícius de França (Brasil, 2025)
Competency management has emerged as a crucial strategy for improving collective performance in organizational environments, especially in sectors such as the Secretaria de Gestão de Pessoas (SEGEP) of the Tribunal de Justiça do Amazonas (TJAM), where employees face daily challenges related to high workloads and the need to meet urgent demands. This study investigates how the development of competencies and skills impacts the collective performance of SEGEP employees, focusing on key competencies such as communication and leadership. Using a qualitative approach and conducted as a case study, the research was based on interviews with employees from different areas of SEGEP. The results reveal that, although competencies such as communication and leadership are fundamental for efficient performance, several challenges arise, including the misalignment between the training offered and the practical demands of the work, the overload of activities and the lack of time to apply the acquired knowledge. The research concludes that strategic competency management, combined with training more aligned with everyday reality and the strengthening of leadership, can generate substantial improvements in efficiency, collective performance and the quality of services provided by SEGEP.